Epistemology of Islamic Education in the Qur'an and Its Urgency in the Development of Islamic Education - Fauzi, Muhamad Restu; Chirzin, Muhammad (FITK UIN Walisongo, 2023)
This paper seeks to shed light on the debate of scientists about the nature of knowledge, its character and sources. The Qur'an is a source of epistemology whose truth cannot be doubted within Islamic tradition. Tracing the function and several verses thematically by analyzing them within the framework of philosophical interpretation, the researchers found that the Qur'an very intensely calls for thinking, contemplating, conducting research and, of course, reading. This research aims to discover in depth the epistemology of Islamic education in the Qur'an and its urgency in the development of Islamic education. This research took a qualitative approach that employed document analysis to obtain data. The results of this study are: (1) Western epistemology consists of rationalism and empiricism schools, while Islamic epistemology consists of bayani schools, burhani schools and 'irfani schools; (2) The approach method in Islamic education's epistemology in the Qur'an consists of rational, intuitive, dialogic, comparative, criticism and 'ibrah methods; (3) The urgency of Islamic education's epistemology in the development of education is to reform Islamic education without eliminating Islamic idealism.